Storytelling Method With The Help Of Straw Dolls To Improve Children Receptive Language Skills In Kindergarten - Sri Ismawati; Santoso; Mochamad Widjanarko (Journal of Psychology and Instruction, 2022)
Children still have difficulties with language. It is because the way children speak could be clearer. This research aims to create a storytelling method with the help of straw dolls to improve children's receptive language development. This type of research is an R&D method. The research subjects consisted of 2 media experts and one material expert, and 45 kindergarten children. The data collection techniques were interviews, observations, questionnaires, and documentation. The data analysis technique used quantitative analysis. The results showed the validity test with n = 10 and a significance score of 5% with r table 0.632. The results obtained were declared valid because r count> r table. The validation test from material experts obtained an average score of 83.75% and 93.75%, including in the very feasible category. In contrast, linguists scored four which was in the very good category. Data analysis to test the effectiveness is shown in the results of the N-Gain calculation in the field test, as the experimental class obtained post-test results of 80.67 and 80.33, respectively. In contrast, for the control class, the post-test obtained a result of 56.00. The conclusion shows that the development of storytelling methods with the help of straw dolls to improve children's language skills in kindergarten is feasible and effective in improving children's language skills. The implications of this research are expected to help teachers improve children's language skills through learning media.